EFEKTIFITAS METODE MODERN WRITTEN ARABIC DALAM MAHARAH KITABAH PADA MAHASISWA IAIN AMBON - Nure Khun Rikhte Husaini (LP2M UIN Abdul Muthalib Sangadji Ambon, 2024)
Kitabah lerning method offered at islamic boarding school, islamic school and university is diverse, but that is difficult to be applied in it. Practis and simple method based on modern written arabic (MWA) comes to simplify complexity in learning kitabah for arabic education student in IAIN Ambon. This method stress that all gramatical arabic formed by vacobulary, frase, sentance and clause. Learning kitabah by this methode to them will give them the significant effect in number of errors in writing arabic literature. It is seem in reducing of writting errors at pre test and post test, specially in shifat frase and idhofah frase.